2011
DOI: 10.1007/s10194-011-0302-z
|View full text |Cite
|
Sign up to set email alerts
|

Focus on the management of thunderclap headache: from nosography to treatment

Abstract: Thunderclap headache (TCH) is an excruciating headache characterized by a very sudden onset. Recognition and accurate diagnosis of TCH are important in order to rule out the various, serious underlying brain disorders that, in a high percentage of cases, are the real cause of the headache. Primary TCH, which may recur intermittently and generally has a spontaneous, benign evolution, can thus be diagnosed only when all other potential underlying causes have been excluded through accurate diagnostic work up. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Efficacy of nimodipine was reported in primary TCH [ 12 ] as well as in primary bathing TCH [ 13 ] with vasospasm detected or non-detected. It has been suggested that primary recurrent TCH can be divided in two groups: one with diffuse vasospasm and the others without any visible vasospasm by MRA, and primary TCH, to some extent, share the same spectrum with reversible cerebral vasoconstriction syndrome (RCVS) based on their similar clinical features and the same rate of ischemic complications [ 14 , 15 ]. The therapeutic efficacy of nimodipine in vasospasm associated primary TCH and RCVS as well as in our micturitional headache may suggest a similar pathogenic mechanism of vasospasm for both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy of nimodipine was reported in primary TCH [ 12 ] as well as in primary bathing TCH [ 13 ] with vasospasm detected or non-detected. It has been suggested that primary recurrent TCH can be divided in two groups: one with diffuse vasospasm and the others without any visible vasospasm by MRA, and primary TCH, to some extent, share the same spectrum with reversible cerebral vasoconstriction syndrome (RCVS) based on their similar clinical features and the same rate of ischemic complications [ 14 , 15 ]. The therapeutic efficacy of nimodipine in vasospasm associated primary TCH and RCVS as well as in our micturitional headache may suggest a similar pathogenic mechanism of vasospasm for both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The management of thunderclap headache depends on the underlying etiology. Primary thunderclap headache has a relatively benign course even without specific management (70). Two prospective studies involving 89 patients with thunderclap headache after excluding SAH who were followed up for 1.7 to 3.3 years demonstrated a very good outcome (71,72).…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Its mechanism of action is anti-inflammatory through reversible inhibition of cyclooxygenase (COX)-1 and -2, but it can inhibit nitric oxide release and decrease cerebral blood flow and cerebrospinal fluid pressure. 29 In case of contraindication to indomethacin or inadequate response, other drugs are used, such as melatonin, onabotulinumtoxin A, gabapentin and topiramate. 2…”
Section: Asaamentioning
confidence: 99%